Simultaneous improvement of the dielectric constant and leakage currents of ZrO2 dielectrics by incorporating a highly valent Ta5+ element. Issue 36 (3rd September 2018) - Park, Bo-Eun; Oh, Il-Kwon; Park, Jong Seo; Seo, Seunggi; Thompson, David; Kim, Hyungjun
Abstract : Ta doping into ZrO2 suppresses the oxygen vacancy formation and changes the crystal structure, leading to simultaneous improvement of dielectric constant and leakage currents. Abstract : Dynamic random access memory (DRAM) is reaching the scaling limit owing to the requirements for a high capacitance density and low leakage current of metal–insulator–metal (MIM) capacitors. We investigated the Ta-doped ZrO2 dielectric as a novel high- k candidate, utilizing the precise control of Ta-doping concentration using the atomic layer deposition (ALD) supercycle process. We systematically studied the chemical composition and crystal structure of ALD Ta-doped ZrO2 and its effects on the electrical properties of MIM capacitors. It was shown that ZrO2 becomes more stoichiometric with the introduction of Ta, which is attributed to the suppression of oxygen vacancy (VO ) formation. The change in the atomic arrangement due to the substitution of Zr with Ta and the reduction of VO enhances the crystallinity of the cubic phase and causes a decrease in the molar volume of the ZrO2 films. As a result of the change in the crystal structure along with the high dielectric polarizability of Ta, the dielectric constant of ALD Ta-doped ZrO2 increases by up to 80% compared to that of undoped ZrO2 films. Moreover, the reduction of the VO species suppresses the emission of the carriers, which lowers the leakage current density by two orders of magnitude in the Ta-doped ZrO2 films as compared to that in the undoped ZrO2 films. In general, the dielectric constant and leakage currents have a trade-off relationship in a single high- k dielectric system. Consequently, proper doping of Ta into ZrO2 using ALD is a promising solution to overcome the technical limits of conventional high- k dielectrics.